BATAS WAKTU PEMBERIAN ZAKAT KEPADA MU’ALLAF: KAJIAN FIQIH KONTEMPORER & USHUL AL-FIQH. - Nur Azizah Rahman (Potret Pemikiran, 2016)
ABSTRACT. Zakat is one of the instruments supporting community economic development. In its instrument of charity will create the spirit of helping (ta'awun) and contains elements of fulfillment, obligations of individuals to give responsibility to the community. Zakat is accomplished with good will cleanse and purify the soul, as well as improving the quality of faith, develop and endow properties. Zakat is well managed and the trust will be able to create community welfare, improve the ethos and work ethic, as well as equitable economic institutions.            At provisions mus}arrif al-zakat there are some groups that a debate about the existence of them, one of them mua'allaf. In the period of the Prophet part is always given for the existence of Muslims is still very small with weak levels of faith. After the Prophet's death, the leadership of which alternates among the Companions, has implications for policy changes from the application of section mu'allaf, some still apply, others may not, for various reasons. Thus, this paper will examine on a time limit charitable giving to mu'allaf in a review of contemporary jurisprudence and us}ul al-fiqh.Keywords: Zakat, mu'allaf, contemporary jurisprudence, us}ul al-fiqh.